Reforming Water Supply in Abidjan, Côte d'Ivoire : Mild Reform in a Turbulent Environment - Ménard, Claude (World Bank, Washington, DC, 2015)
Compared with other urban water systems in West Africa, the water supply system in Abidjan performs very well. Documenting the recent history of that system, the authors try to answer three questions: What motivated reform in a system that was already performing well? How and why did the reform affect sector performance, and what additional changes might improve performance further? And what explains the relatively strong performance of Abidjan's water system? Is the success attributable primarily to an efficient contractual arrangement or more generally to Cote d'Ivoire's institutional environment? In a region plagued by political instability, Ivorian political institutions were remarkably stable for close to 40 years. In part, the success of the Ivorian model is the result of these institutions' stability and credibility. The single-party system in place at the time of reform might suggest that there were few restraints in place to prevent the government from behaving opportunistically. But several features of the institutional environment protected against such opportunism. Because of this, and because reform was based on a system already performing well, the contractual arrangement with a private operator proved exceptionally capable of adjusting even in the face of dramatic changes in the external environment. Institutional environments are not as favorable in other countries in the region, so similar contractual arrangements might be less successful elsewhere. Reform in Cote d'Ivoire was motivated primarily by a macroeconomic crisis, which reduced the resources available for public investment. Without either a sector crisis or a realignment of political forces, the will for reform was weak. Consequently, opportunities for improvement were missed and some problems remain. Among other ways in which the system could be improved: Splitting the water system into autonomous subsystems in different cities, and allowing bidding for investment contracts, would increase the chances of competition for investment, which does not currently exist.